2023
DOI: 10.3390/molecules28176391
|View full text |Cite
|
Sign up to set email alerts
|

Knotwood and Branchwood Polyphenolic Extractives of Silver Fir, Spruce and Douglas Fir and Their Antioxidant, Antifungal and Antibacterial Properties

Pauline Gérardin,
David Hentges,
Philippe Gérardin
et al.

Abstract: The extractive contents of three softwood species largely used in the wood industry, namely Abies alba (Silver fir), Picea abies (spruce) and Pseudotsuga menziesii (Douglas fir), have been determined quantitatively for knots and at different points chosen along their branches, before analysis using high-performance liquid chromatography coupled with Mass Spectrometry (HPLC-MS). The results indicated that branchwood samples located in close proximity to the stem present high contents of extractives similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A single method of analysis, however, may not provide a comprehensive understanding of the antioxidant activity of the extract we studied. For a more precise approach, it is necessary to use other assays in the future to capture the full spectrum of antioxidant activity [10,11,14,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single method of analysis, however, may not provide a comprehensive understanding of the antioxidant activity of the extract we studied. For a more precise approach, it is necessary to use other assays in the future to capture the full spectrum of antioxidant activity [10,11,14,63].…”
Section: Discussionmentioning
confidence: 99%
“…Spruce is traditionally used for its anti-inflammatory and antiseptic action, in respiratory and skin diseases as different pharmaceutical preparations: syrup, tea, creams, ointments, and baths [4]. Recent clinical studies have shown antibacterial and antifungal properties [11,12], wound healing [13], immunological, anti-inflammatory and antioxidant effects [14][15][16] and even antitumoral action [17][18][19] for the spruce, due to its bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening highlighted the presence of several families of extractives such as flavonoids, tannins and polyphenols, which are reported in the literature to possess strong antioxidant properties [38,39,47,48]. In addition, GC-MS analysis indicated different phenolic compounds such as catechin, 3,4-dihydroxybenzaldehyde, 4-hydroxybenzoic acid, isovanillic acid or protocatechuic acid, which may be also responsible for antioxidant activity.…”
Section: Antioxidant Testsmentioning
confidence: 96%
“…Polyphenols such as lignans have antifungal and antioxidant properties. They are studied for pharmaceutical and nutraceutical applications [38,39]. Saponins have many applications in the food and cosmetic industry due to their foaming properties.…”
Section: Phytochemical Testsmentioning
confidence: 99%